Combined "top-down" and "bottom-up" intervention for anxiety sensitivity: Pilot randomized trial testing the additive effect of interpretation bias modification. (February 2017) - Capron, Daniel W.; Norr, Aaron M.; Allan, Nicholas P.; Schmidt, Norman B.
Abstract: Objective: Anxiety disorders contribute substantially to the overall public health burden. Anxiety sensitivity (AS), a fear of anxiety-related sensations, is one of the few known malleable risk factors for anxiety pathology. Previous AS reduction treatments have primarily utilized "top-down" (e.g., psychoeducation) interventions. The goal of the current study was to evaluate the effect of adding a "bottom-up" (interpretation bias modification; CBM-I) intervention to an AS psychoeducation intervention. Design: Single-site randomized controlled trial. Participants completed either a 1) Psychoeducation + active CBM-I or 2) Psychoeducation + control CBM-I intervention. Change in AS was assessed post-intervention and at a one-month follow-up. Participants: Individuals with elevated levels of AS. Intervention: Single-session computer-delivered intervention for AS. Results: Accounting for baseline ASI-3 scores, post-intervention ASI-3 scores were significantly lower in the combined condition than in the psychoeducation + control CBM-I condition (β = 0.24, p < 0.05; d = 0.99). The active CBM-I plus psychoeducation AS intervention was successful in reducing overall AS (59% post-intervention; p < 0.05, Cohen's d = 0.99) and these reductions were maintained through one-month post-intervention (52%; p < 0.05, Cohen's d = 1.18). Participants in the active condition reported significantly lower rates of panic responding to a vital-capacity CO2 challenge (OR = 6.34, 95% CI = 1.07–37.66). Lastly, change in interpretation bias significantly mediated the relationship between treatment condition and post-treatment AS reductions. Conclusions: The current intervention was efficacious in terms of immediate and one-month AS reductions. Given its brevity, low-cost, low-stigma and portability, this intervention could lead to reducing the burden of anxiety disorders.